The Effect of Trust on Customer Loyalty through Customer Satisfaction - Susanto, Erlans Firman; Pandjaitan, Dorothy Rouly Haratua (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The growth of the tourism sector in Indonesia, particularly in the fast-food restaurant industry, has created significant investment opportunities. The phenomenon of lifestyle changes in urban communities, where time is a crucial factor, has driven interest in convenient and easily accessible fast-food. McDonald's, as a key player in this industry, continues to develop adaptive marketing strategies by introducing innovations and attractive promotions. Customer trust and satisfaction are the keys to maintaining and expanding market share. This research aims to investigate the influence of trust on customer satisfaction and loyalty, and whether trust affects customer loyalty through customer satisfaction, focusing on McDonald's consumers in Bandar Lampung. A quantitative research method with a deductive approach was employed, and a sample of 110 respondents was selected using purposive sampling. Data analysis involved statistical methods and the Smartpls 4.0 application. The research results indicate that trust has a positive and significant impact on customer satisfaction and loyalty. The implications of these findings provide insights for companies, especially McDonald's, to enhance customer trust and satisfaction in efforts to maintain competitiveness in the competitive fast-food industry.